Male engagement as a strategy to improve utilization and community-based delivery of maternal, newborn and child health services: evidence from an intervention in Odisha, India. Issue 1 (December 2015) - Fotso, Jean; Higgins-Steele, Ariel; Mohanty, Satyanarayan
Abstract Background In response to persistently poor levels of maternal, newborn and child health (MNCH) in rural India, the National Rural Health Mission (NRHM) was launched to support the provision of accessible, affordable and quality health care in deprived and underserved communities. The Accredited Social Health Activists (ASHAs), local women, are trained as health promoters to generate demand for, and facilitate access to MNCH care in their communities. While they are also expected to provide husbands of expectant women with information on MNCH care and family planning, their reach to the husbands is limited. The aim of this study is to describe the influence of a male engagement project on the utilization and community-based delivery of MNCH care in a rural district of the country. Methods We used qualitative data from the evaluation of a project which recruited and trained male Community Health Workers (CHWs) known as Male Health Activists (MHAs) to complement the work of ASHAs and target outreach to men. This paper uses data from in-depth interviews (IDIs) with ASHAs (n=11), Anganwadi Workers (AWWs) (n=4) and Auxiliary Nurse Midwives (ANMs) (n=2); with women who had delivered at home, community health center or district hospital in the few months preceding the date of the interview (n=11); and with husbands of these women (n=7). Results Participants' responses are broadly organized around the facilitation of ASHAs' work by MHAs, and male engagement activities undertaken by MHAs. More specifically, the narratives reflected gender-based divisions of work and space in three core areas of delivery and use of MNCH services: escorting women to health centers for facility-based deliveries; mobilizing women and children to attend Village Health and Nutrition Days and Immunization Days; and raising awareness among men on MNCH and family planning. Conclusion This study sheds light on male engagement as a strategy to improve the delivery, access and uptake of maternal, newborn and child health in the context of prevailing gender norms and gendered roles in rural India. Ultimately, it unveils the complementarity of male and female CHWs in the community-based delivery of, and increased demand for, MNCH services.